Quality of life of informal caregivers of aged people with alzheimer's disease during the COVID-19 pandemic - Nascimento, Monique Teresa Amoras; Carvalho, Dayara de Nazaré Rosa de; Lima, Fernando Conceição de; Bendelaque, Dandara de Fátima Ribeiro; Sousa, Fabianne de Jesus Dias de; Orlandi, Fabiana de Souza; Aguiar, Viviane Ferraz Ferreira de (Revista de Enfermagem da UFPI, 2023)
Objective: To reveal the quality of life of informal caregivers of aged people with Alzheimer's disease in times of the COVID-19 pandemic. Method: A descriptive and qualitative study conducted through semi-structured interviews with 12 informal caregivers of older adults, selected by convenience. Data processing was performed using the IraMuTeQ software and class analysis using the Strauss and Corbin method, from which 4 classes emerged, namely: Social network and change in the routine of informal caregivers during the COVID-19 pandemic period; Factors that interfere with the QoL of informal caregivers; How informal caregivers experience the Alzheimer's disease diagnosis; and Feelings awakened by the burden of informal caregivers of aged people with AD. Results: The female profile stood out, with emphasis on caregivers aged from 40 to 49 years old, married, incomplete High School, and performing this role for more than five years and full-time. The factors that interfere with quality of life are lack of time, care burden, lack of leisure, few social activities and feelings of sadness, anxiety, nervousness, depression and despair. Conclusion: It was verified that the aspects found were impacted even more during the COVID-19 pandemic period, which reconfigured the routine of older adults with Alzheimer's and of...